The Story of Slavery - Sarah Courtauld (London Usborne Publishing, 2007)
A compelling account of the story of slavery from ancient times, through the sugar plantations of the Caribbean and America to the slave trade's official abolition 200 years ago. Recounts the stories of individual slaves, including their journeys and escape stories, and the slave trade in the 21st century
Include Color Illustration and Index
Keywords: Slave trade -- Slavery